Effect of Metformin on Renal Function After Primary Percutaneous Coronary Intervention in Patients Without Diabetes Presenting with ST-elevation Myocardial Infarction: Data from the GIPS-III Trial - Posma, Rene A. (Cardiovasc Drugs Ther, 2015)
PURPOSE: The association between metformin use and renal function needs further to be elucidated since data are insufficient whether metformin affects renal function in higher risk populations such as after ST-elevation myocardial infarction (STEMI). METHODS: We studied 379 patients included in the GIPS-III trial in which patients without diabetes or renal dysfunction, who underwent primary percutaneous coronary interventions (PCI) for STEMI, were randomized to metformin 500 mg or placebo twice daily for four months. At baseline and at seven scheduled visits up to four months after PCI, estimated glomerular filtration rate (eGFR) was determined (2582 values). Contrast-induced acute kidney injury (CI-AKI) was defined as an increase in serum creatinine of ≥0.3 mg/dl or 25 % rise within 48 h after PCI. RESULTS: At all visits, the mean eGFR was similar in patients randomized to metformin or placebo. Over the four month period, mixed-effect repeated-measures model analysis showed a least-squares mean ± standard error change in eGFR of -5.9 ± 0.8 ml/min/1.73 m(2) in the metformin group and −7.1 ± 0.8 ml/min/1.73 m(2) in the control group (P = 0.27 for overall interaction). The incidence of CI-AKI was 14.8 %; 29 (15.2 %) patients in the metformin group versus 27 (14.4 %) controls (P = 0.89). After adjustment for covariates, metformin treatment was not associated with CI-AKI (odds ratio: 0.96, 95%CI 0.52 − 1.75, P = 0.88). CONCLUSION: We conclude that initiation of metformin shortly after primary PCI has no adverse effect on renal function in patients without diabetes or prior renal impairment, further providing evidence of the safety of metformin use after myocardial infarction and subsequent contrast exposure. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10557-015-6618-1) contains supplementary material, which is available to authorized users.